An auxiliary frequency tracking system for general purpose lock-in amplifiers. (8th March 2018) - Xie, Kai; Chen, Liuhao; Huang, Anfeng; Zhao, Kai; Zhang, Hanlu
Abstract: Lock-in amplifiers (LIAs) are designed to measure weak signals submerged by noise. This is achieved with a signal modulator to avoid low-frequency noise and a narrow-band filter to suppress out-of-band noise. In asynchronous measurement, even a slight frequency deviation between the modulator and the reference may lead to measurement error because the filter's passband is not flat. Because many commercial LIAs are unable to track frequency deviations, in this paper we propose an auxiliary frequency tracking system. We analyze the measurement error caused by the frequency deviation and propose both a tracking method and an auto-tracking system. This approach requires only three basic parameters, which can be obtained from any general purpose LIA via its communications interface, to calculate the frequency deviation from the phase difference. The proposed auxiliary tracking system is designed as a peripheral connected to the LIA's serial port, removing the need for an additional power supply. The test results verified the effectiveness of the proposed system; the modified commercial LIA (model SR-850) was able to track the frequency deviation and continuous drift. For step frequency deviations, a steady tracking error of less than 0.001% was achieved within three adjustments, and the worst tracking accuracy was still better than 0.1% for a continuous frequency drift. The tracking system can be used to expand the application scope of commercial LIAs, especially for remote measurements in which the modulation clock and the local reference are separated.